2012
DOI: 10.1002/marc.201200153
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Induced Shape‐Memory Polymers

Abstract: A novel pH sensitive shape‐memory polymer (SMP) is prepared by cross‐linking the β‐cyclodextrin modified alginate (β‐CD‐Alg) and diethylenetriamine modified alginate (DETA‐Alg): The pH reversible β‐CD‐DETA inclusion complexes serve as a reversible phase, and the cross‐linked alginate chains serve as a fixing phase. It is shown that this material can be processed into temporary shape as we needs at pH 11.5 and recover to its initial shape at pH 7. The recovery ratio and the fixity ratio were 95.7 ± 0.9% and 94.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
168
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(168 citation statements)
references
References 24 publications
0
168
0
Order By: Relevance
“…When the hydrophobicity or size of the guest molecule is changed upon exposure to an external stimulus such as light, redox and pH, the complexes would show a reversible assembly-disassembly behavior. An example using the host-guest complex as the molecular switches was recently reported by Zhang and coworkers [131]. They synthesized crosslinked alginate networks containing both β-CD and diethylenetriamine (DETA) as the side groups (Fig.…”
Section: Page 21 Of 106mentioning
confidence: 97%
“…When the hydrophobicity or size of the guest molecule is changed upon exposure to an external stimulus such as light, redox and pH, the complexes would show a reversible assembly-disassembly behavior. An example using the host-guest complex as the molecular switches was recently reported by Zhang and coworkers [131]. They synthesized crosslinked alginate networks containing both β-CD and diethylenetriamine (DETA) as the side groups (Fig.…”
Section: Page 21 Of 106mentioning
confidence: 97%
“…A diverse array of SMPs have been developed that recover their permanent shape in response to light [2], magnetic fields [3], electricity [4], moisture [5], or pH [6] for a variety of industrial, aeronautical, and biomedical applications and can be reviewed elsewhere [1, 7, 8]. In contrast to their shape memory alloy counterparts, SMPs can be created with diverse, multi-functional chemistries to enable drastic yet highly-controllable shape responses to various stimuli [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Liu 28 and Yang 29 utilized Zn 2+ –imidazole and Fe 3+ –phosphate coordination respectively to construct hydrogels with shape memory behavior. Zhang 31 and Harada 32 recently showed that host–guest complexes between dextrin and guest molecules such as adamantine and ferrocene can also be applied to fix temporary shapes. These pioneering works are tremendously useful to inspire the design of novel SMPs on the basis of supramolecular interactions.…”
Section: Introductionmentioning
confidence: 99%